2011
DOI: 10.1002/ptr.3565
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ephedra Water Decoction and Cough Tablets containing Ephedra and Liquorice on CYP1A2 and the Pharmacokinetics of Theophylline in Rats

Abstract: Ephedra water decoction (EWD) and cough tablets containing ephedra and liquorice (maxing cough tablets, MXCT) have been used widely in the treatment of asthma. In the clinic, EWD and MXCT may be prescribed with theophylline, one of the most popular antiasthmatic drugs and a typical substrate of cytochrome P450 (CYP) 1A2. So in the present study the potential effects of EWD and MXCT on CYP1A2 activity and the pharmacokinetics of theophylline in rats were evaluated. In the in vivo CYP1A2 activity research, the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…In one study, G. uralensis had an induction effect on P450 isozymes both in vivo and in vitro (Tang et al, 2009). The inhibitory effects of glycyrrhetinic acid on all tested isoforms of uridine 5′-diphospho-glucuronosyltransferases (UGTs), including 1A3 and 2B7, have been reported; thus, the possibility of an herb-drug interaction with Theophylline Speeded up the metabolism of theophylline by inducing CYP1A2 activity in rats (Tang et al, 2012) CL, clearance; AUC, area under the curve; t 1/2 β, half-time; MRT, mean residence time; MTX, methotrexate; Cp, plasma concentration; 11β-HSD-2, 11β-hydroxysteroid dehydrogenase-2; P-gp, P-glycoprotein. a Cough tablet ephedra and licorice.…”
Section: Drug Interactionmentioning
confidence: 99%
“…In one study, G. uralensis had an induction effect on P450 isozymes both in vivo and in vitro (Tang et al, 2009). The inhibitory effects of glycyrrhetinic acid on all tested isoforms of uridine 5′-diphospho-glucuronosyltransferases (UGTs), including 1A3 and 2B7, have been reported; thus, the possibility of an herb-drug interaction with Theophylline Speeded up the metabolism of theophylline by inducing CYP1A2 activity in rats (Tang et al, 2012) CL, clearance; AUC, area under the curve; t 1/2 β, half-time; MRT, mean residence time; MTX, methotrexate; Cp, plasma concentration; 11β-HSD-2, 11β-hydroxysteroid dehydrogenase-2; P-gp, P-glycoprotein. a Cough tablet ephedra and licorice.…”
Section: Drug Interactionmentioning
confidence: 99%
“…In recent years, there has been a significant increase in the clinical use of combinatorial intervention in TCM to achieve synergistic interactions that are capable of producing a sufficient effect at low doses (Singh et al ., ). Pharmacokinetics and pharmacodynamics may play a key role in the evaluation of drug action and be regarded as available means in elucidating the mechanism of a TCM formulae (Tang et al ., ; Jin et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study demonstrated that EWD or MXCT pretreatment obviously induced CYP1A2 activity in vivo by speeding up the metabolism of theophylline (Tang et al, 2012). CYP1A2 and CYP2E1 are mainly involved in the oxidative metabolism of theophylline in human liver (Gu et al, 1992;Paolini et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…In our previous study, ephedra water decoction (EWD) or MXCT pretreatment obviously induced CYP1A2 activity and speeded up the metabolism of theophylline (Tang et al, 2012). Therefore, the current study was conducted to investigate the effect of EWD or MXCT on CYP1A2 and CYP2E1 hepatic enzymes in the protein level and mRNA level, and the activity of CYP1A2 and CYP2E1 was assessed ex vivo in rats.…”
Section: Introductionmentioning
confidence: 99%